2009
DOI: 10.1002/bdd.684
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of uptake of metformin and phenformin mediated by hOCT1 in human hepatocytes

Abstract: Metformin, a biguanide that has been used to treat type 2 diabetes mellitus, is reportedly transported into human hepatocytes by human organic cation transporter 1 (hOCT1). The objective of this study was to investigate differences in the hepatic uptake of metformin and phenformin, a biguanide derivative similar to metformin. Special focus was on the role of active transport into cells. Experiments were therefore performed using human cryopreserved hepatocytes and hOCT1 expressing oocytes. Both biguanides prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Previously, phenformin has been used at a concentration of up to 10 mM to determine AMPK regulation in rat skeletal muscle [37]. In addition, phenformin has been shown to be rapidly transported in hepatocytes, compared with metformin [35]. In the present study ( Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Previously, phenformin has been used at a concentration of up to 10 mM to determine AMPK regulation in rat skeletal muscle [37]. In addition, phenformin has been shown to be rapidly transported in hepatocytes, compared with metformin [35]. In the present study ( Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Importantly, Zhou et al have shown that in rat hepatocytes, metformin exhibits significant biological effects at 500 μM to 3 mM concentrations upon incubation for 1 to 3 hours [34]. This has been attributed to its slow membrane permeability / transport in hepatocytes [34, 35]. In the present study, we therefore incubated aortic rings with metformin at 10 μM to 3 mM concentrations for 30 min ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Hepatic uptake by OCT1 and passive permeability in the liver were applied in the PerL model using estimates of intrinsic clearance and CL PD,liver , respectively, from experiments with cryopreserved human hepatocytes (Sogame et al, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More recently, another group reported that the inhibition of mTOR1 by metformin was due to the enhanced binding between PRAS40 and Raptor, both of which are components of mTORC1, thus independent of AMPK (20). The second concern is that intake of metformin into the cell requires the expression of OCT1 (organic cation transporter 1) (21,22), and the concentrations of metformin used in current in vitro or preclinical antiproliferative studies are much higher than the recommended therapeutic dose in humans (23). In other words, the positive results in animal studies cannot indicate success in clinical trials if we do not use a similar dose of metformin.…”
mentioning
confidence: 99%